التحليل النفسي عند سيغموند فرويد في قصيدة "أحبكِ جدًّا" لنزار قباني - Kinanti, Keyla Azzahra Rizki; Prastika, Khalysta Geovanny; Djailani, Mohamad Rivzal (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study aims to analyze psychological conflicts in the poem "uhibbuka jiddan" by Nizar Qabbani using Sigmund Freud's psychoanalytic approach. The method used is qualitative descriptive with the technique of text analysis of poetry stanzas. The results of the study show that lyrical characters experience conflicts between three personality structures, namely id, ego, and superego. The id appears in a strong, irrational love impulse, while the ego seeks to conform those desires to an impossible reality. The superego is present through awareness of the norms and conditions that limit the relationship. The dominance of the id causes the character to maintain his feelings, even though it is contrary to reality. To relieve inner tension, the character uses self-defense mechanisms such as idealization, fantasy, and denial. Thus, this poem represents the dynamics of the human psyche in the face of unfulfilled love and shows the complexity of the relationship between emotional impulses and social reality.